The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1108/ijoes-03-2018-0042
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of corporate environmental disclosure quality of oil and gas industry in developing countries

Abstract: Purpose -This study aims to identify factors that influence corporate environmental disclosure (CED) quality. Design/methodology/approach -Using content analysis, an index and scoring scheme were applied to annual reports, stand-alone reports and corporate homepages of a sample of 116 oil and gas companies in 19 developing countries (DCs).Findings -The results of this study reveal that out of 12 hypothesized variables, only 5 variables (company size, foreign ownership, profitability, leverage and membership of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
69
0
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 101 publications
(198 reference statements)
18
69
0
17
Order By: Relevance
“…Rahmawati & Budiwati (2018) proved that the EMS has a significant and positive effect on the disclosure of environmental information. This finding is consistent with the finding of Bawono & Hayanto (2015) but different from Ismail et al (2018) who revealed that EMS has no significant effect on environmental disclosure.…”
Section: Introductionsupporting
confidence: 90%
See 4 more Smart Citations
“…Rahmawati & Budiwati (2018) proved that the EMS has a significant and positive effect on the disclosure of environmental information. This finding is consistent with the finding of Bawono & Hayanto (2015) but different from Ismail et al (2018) who revealed that EMS has no significant effect on environmental disclosure.…”
Section: Introductionsupporting
confidence: 90%
“…The operational definitions of the variables in this study can be seen in Table 2. Disclosure of environmental information items carried out by companies (Solikhah & Winarsih, 2016) Content analysis (Raar, 2002;Wahyuningrum & Budihardjo, 2018) Return on Equity (ROE) Indicators of corporate financial performance in generating profits using its own capital (Lampe, 2013) x100% (Buallay, 2019;Lampe, 2013) Net Profit Margin (NPM) Profitability ratio to calculate net profit margin of a company (Liu et al, 2013) x 100% (Liu et al, 2013) x 100% (Lampe, 2013) Firm Size (SIZE) Large or small size of a company (Irawati, 2012) LN ( (Ismail et al, 2018) Industry Type (TYPE) Industry type based on its sensitivity to the environment (Djajadikerta & Trireksani, 2012) 1 = high profile 0 = low profile (Wahyuningrum & Budihardjo, 2018) Source: Various references, 2019…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations